Science for the Chinese Common Reader? Myriad Treasures and New Knowledge at the Turn of the Twentieth Century. Issue 3 (11th October 2017) - Judge, Joan
Argument: This article argues that in order to discern the place of science in the epistemology of Chinese common readers, it is critical to look beyond the coastal enclaves where foreign missionaries and experts interacted with Chinese scholars and officials, beyond the translated treatises they produced, and even beyond the various forms of new media that attempted to more widely disseminate the principles of Western science. Instead, it asserts the need to engage a different register of materials that were less directly tied to foreign expertise, more directly in line with pre-existing lineages of printed materials, and at the same time, integral to early-twentieth-century Chinese circuits of information. The article focuses explicitly on one print phenomena that has been completely overlooked in the scholarship to date, the expansion and revitalization of the genre of texts known as wanbao quanshu 萬寶全書 (comprehensive compendia of myriad treasures) in the late Qing (1890-1911) and early Republic (1912-1930).